EFEKTIVITAS SOCIAL MEDIA INSTAGRAM #PASARSENENUKM TERHADAP PENINGKATAN PROMOSI UKM DI INDONESIA - Wardhani, Alysha Tri; Uljanatunnisa, Uljanatunnisa; Hendrayani, Yani (POPULIKA, 2020)
#PasarsenenUKM Service is a service on Instagram social media that made public relations Ministry of SME and RI. The purpose this research is to know how much Social Media effectiveness Instagram #pasarsenenUKM to increase promotion of SMES in Indonesia. The theory used is The Hierarchy of Effects Concept, this theory explains the steps that consumers take to make decisions. The method used is quantitative with this type of an expreslanative research. The chosen population is an Instagram followers @KemenkopUKM as much as 186,000 people, using Yamane formula and then obtained the sample number of 100 respondents. This research uses questionnaire deployment techniques to get data. Based on the calculation Â the test results T obtained t count 11.921 > T table 1.661, it can be concluded that Ho rejected and Ha accepted meaning that Social Media effectiveness the Instagram #pasarsenenUKM has significant influence on the improvement of SME promotion in Indonesia.